Analisis Penilaian Kinerja terhadap Pendidik dan Tenaga Kependidikan pada SDIT At-Taqwa 2 Surabaya - Fauziyah, Hikmatul; H.P, Berlian Therapi; Ilyas, M. Effendi (ARZUSIN, 2023)
This study aims to find out how the performance appraisal conducted by SDIT At-Taqwa 2 Surabaya, on educators and their educational staff. Educators and educational staff are an important part of the running of the educational process, where it must be able to run well. The method used in writing this article is descriptive qualitative method of data collection and literature study. With the analysis that has been carried out by researchers, the following results are found, 1) What are the steps taken by the school principal in determining qualified teaching and educational staff. 2) Obstacles encountered in the process of assessing educators and educational staff, namely the difficulty of male teaching staff. 3) How do educators overcome the difficulties experienced by students. 4) Factors in the success of education at SDIT At-Taqwa 2. 5) There are teaching staff but not in accordance with the required criteria. 6) There are some educators who cannot recite properly and correctly 7) Institutions that are still relatively new and lack experience in learning. 8) Almost all teaching staff have not been certified by the education office. And so forth.